The effects of hydrostatic pressure on the spontaneous release of transmitter at the frog neuromuscular junction. - Ashford, M L (1982)
1. The effects of hydrostatic pressure (0.1-15.55 MPa) on the spontaneous release of transmitter at the frog neuromuscular junction were investigated. 2. The major effect of high pressure is on the release mechanism, pressure (0.1-10.40 MPa) producing an exponential decrease in frequency of the miniature end-plate currents in normal Ringer solution. The frequency decreases to 0.52 and 0.24 of the control value at 5.25 and 10.40 MPa respectively. This effect is reversible on decompression. 3. The sensitivity of the release process to high pressure is unaltered in 10 mM-K+, 6 mM- and 10 mM-Ca2+ and hypertonic (165 mM-NaCl) Ringer solution, although the high Ca2+ media shift the threshold for the pressure effect to higher pressures. 4. Higher pressure (10.40-15.55 MPa) produces a small increase in the time constant of decay (tau D) of m.e.p.c.s with no effect on the growth phase. A pressure of 15.55 MPa increases tau D to 1.35 of the control value. 5. The possible actions of high pressure on both the pre- and post-synaptic processes are briefly discussed.